Studi Fenomenologi Pengalaman Guru dalam Mengembangkan Ketrampilan Sosial Siswa Sekolah Dasar saat Pandemi Covid-19 - Putri Rachmadyanti; Hendrik Pandu Paksi; Vicky Dwi Wicaksono; Suprayitno Suprayitno; Ganes Gunansyah (Universitas Kanjuruhan Malang, 2022)
The purpose of this study was to describe the experiences of elementary school teachers in developing students' social skills during online learning during the covid-19 pandemic. This study was explored using a qualitative approach with a phenomenological type of study, by examining the experiences of 10 elementary school teachers in developing students' social skills. Data collection in this study used semi-structured interview techniques. The teacher's strategy in forming groups based on the distance between students' homes, making it easier for students to work with their teams. The learning method used to develop social skills is discussion and assignment. The teacher gave reinforcement verbally, using words to motivate students. Classroom management to run effectively and efficiently includes making class rules, giving examples and habituation. Teachers agree that learning social skills is very important in preparing students to live in society.